Analisis Kinerja Keuangan atas Pelaksanaan Anggaran Pendapatan dan Belanja Dengan Penerapan Value for Money Pada UPTD Pengujian Kendaraan Bermotor Kota Palembang - Desti Wulandari; Feronika Rosalin (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2019)
The dynamics of the development of the organizational environment both internally and externally is very influential on the success or failure of an organization in achieving performance as expected. Through performance measurement, the success of an organization both government can be seen with the ability of the government or agency to manage resources optimally so that the expected results match with a plan outlined in strategic planning. This study aims to analyze financial performance at the UPTD for Motor Vehicle testing in the City of Palembang by applying the concept of value for money. Data collection is taken from the budget and income reports, and interviews with the UPTD Testing of Motor Vehicles in Palembang. This uses three measuring instruments, namely economical, efficient, and effectiveness. The results of this study indicate that the financial performance of the UPTD for testing motor vehicles in Palembang in 2017 shows the ratio of economists i amounted to 102.31% (economical), the efficient ratio was 127.04% (inefficient) and the effectiveness ratio was 146.18% (effective).